2020
DOI: 10.1002/adma.202003238
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of Carbon Dioxide Driven by the Intrinsic Defects in the Carbon Plane of a Single Fe–N4 Site

Abstract: various noble metal catalysts, such as Au, Ag, and Pd have demonstrated impressive potential for yielding CO through CO 2 RR. [2] Furthermore, Ir/Au [1a] and 3D Pd nanosheets [3] offer sufficient performances for Zn-CO 2 batteries. These electrocatalysts are, however, expensive and often require high overpotentials to generate desired products. In addition, the Faradaic efficiency (FE) for CO 2 RR in Zn-CO 2 batteries, particularly for CO 2-to-CO conversion, is typically below 50% at relatively high discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
186
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(193 citation statements)
references
References 63 publications
7
186
0
Order By: Relevance
“…defects (DNG-Fe-N 4 ) for dramatically improving CO 2 RR activity (Figure 17). [231] They further experimentally verified the existence of intrinsic carbon defects by EPR and Raman. In contrast to the above results, they found that the CO 2 RR activity originates from carbon defects rather than traditional Fe-N 4 sites.…”
Section: Creating Vacancy/edge Defectsmentioning
confidence: 94%
See 2 more Smart Citations
“…defects (DNG-Fe-N 4 ) for dramatically improving CO 2 RR activity (Figure 17). [231] They further experimentally verified the existence of intrinsic carbon defects by EPR and Raman. In contrast to the above results, they found that the CO 2 RR activity originates from carbon defects rather than traditional Fe-N 4 sites.…”
Section: Creating Vacancy/edge Defectsmentioning
confidence: 94%
“…Reproduced with permission. [231] Copyright 2020, Wiley-VCH. could form the mixing-coordinated Ni-N 3 O structure within 2D carbon nanosheets at 500 °C, and further heating to 800 °C generated abundance carbon vacancies with Ni-N 3 .…”
Section: Creating Vacancy/edge Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through different synthesis methodologies, graphitic carbon nitride (g-N 3 C 4 ) has been transformed as a raw material for obtaining carbonaceous matrices [129][130][131][132][133]. Li and co-workers [129] used topochemical transformation by carbon layer as a synthesis methodology, which allowed them to ensure the preservation in the structure of Ni-N 4 sites with a homogeneous distribution on the carbon sheets and avoided the agglomeration of Ni atoms to particles, thus allowing to obtain abundant active sites and, consequently, a maximum FE (CO) of 99% at −0.81 V, with a current density of 28.6 mA cm −2 .…”
Section: Smas-n-other Carbon Materialsmentioning
confidence: 99%
“…The main achievement of this synthesis methodology is that it allows controlling the content of Ni single atoms, obtaining an optimum metal content that is crucial for high electrochemical performances in CO 2 electrochemical reduction [132]. Ni and co-authors [133] investigated the influence of intrinsic defects in the carbon plane on catalytic activity, however intrinsic defects in the carbon plane are formed during the pyrolysis process together with other actives sites such as M-Nx and doped nitrogen species, making it a challenge to exclusively study their effect. To do this, they designed two catalysts with two different pyrolysis temperatures (800 • C and 900 • C), using carbon-rich graphitic carbon nitride (C-g-C 3 N 4 ) that served as template and carbon resource during the pyrolysis process.…”
Section: Smas-n-other Carbon Materialsmentioning
confidence: 99%